Natural killer T cells in adipose tissue prevent insulin resistance - Schipper, Henk S.; Rakhshandehroo, Maryam; van de Graaf, Stan F.J.; Venken, Koen; Koppen, Arjen; Stienstra, Rinke; Prop, Serge; Meerding, Jenny; Hamers, Nicole; Besra, Gurdyal; Boon, Louis; Nieuwenhuis, Edward E.S.; et al. (The Journal of clinical investigation, 2012)
Lipid overload and adipocyte dysfunction are key to the development of insulin resistance and can be induced by a high-fat diet. CD1d-restricted invariant natural killer T (iNKT) cells have been proposed as mediators between lipid overload and insulin resistance, but recent studies found decreased iNKT cell numbers and marginal effects of iNKT cell depletion on insulin resistance under high-fat diet conditions. Here, we focused on the role of iNKT cells under normal conditions. We showed that iNKT cell-deficient mice on a low-fat diet, considered a normal diet for mice, displayed a distinctive insulin resistance phenotype without overt adipose tissue inflammation. Insulin resistance was characterized by adipocyte dysfunction, including adipocyte hypertrophy, increased leptin, and decreased adiponectin levels. The lack of liver abnormalities in CD1d-null mice together with the enrichment of CD1d-restricted iNKT cells in both mouse and human adipose tissue indicated a specific role for adipose tissue-resident iNKT cells in the development of insulin resistance. Strikingly, iNKT cell function was directly modulated by adipocytes, which acted as lipid antigen-presenting cells in a CD1d-mediated fashion. Based on these findings, we propose that, especially under low-fat diet conditions, adipose tissue-resident iNKT cells maintain healthy adipose tissue through direct interplay with adipocytes and prevent insulin resistance.